The Effect of Electroacupunctur on Blood Pressure, Mean Arterial Pressure and Pulse Pressure in Hypertensive Patients: Literature Review - Taufik Septiawan; Muhammad Kamil; Hamsih Hamsih; Dinda Ayu Framaisella (GLOBAL HEALTH SCIENCE GROUP, 2021)
A person who has uncontrolled hypertension has seven times greater risk to have a stroke and three times greater risk to have a heart attack. Electroacupuncture therapy is one of the non-pharmacological therapies that can be used as a solution to control blood pressure values ​​in hypertensive patients. This research was conducted to analyze the effect of electroacupuncture therapy on the values ​​of blood pressure, Mean Arterial Pressure, and Pulse Pressure in hypertensive patients. This research used a Literature Review design with journal searches using Science Direct, PubMed, and Google Schoolar published in 2009-2020. Among the 17944 articles obtained, 15 articles were taken for analysis. Furthermore, the Journal Reviews was done by employing the Duffy 2005 Research Apraisal Critical Format. The results of this study found that 9 journals of electroacupuncture and 6 journals of acupuncture showed positive results in which there was an effect of electroacupuncture therapy on the value of blood pressure, mean artery pressure and pulse pressure in hypertensive patients. The researchers concluded that Electroacupuncture therapy affects the value of blood pressure, mean artery pressure, and pulse pressure in hypertensive patients.